A novel model for hemolysis estimation in rotating impeller blood pumps considering red blood cell aging - Wang, Liang; Yun, Zhong; Yao, Jinfu; Tang, Xiaoyan; Feng, Yunhao; Xiang, Chuang (Frontiers in Physiology, 2023)
For rotating vane structure blood pumps, hemolysis values are estimated using a stress-based power-law model. It has been reported that this method does not consider the red blood cell (RBC) membrane's shear resistance, leading to inaccurate estimates of the hemolysis value. The focus of this study was to propose a novel hemolysis model which can more accurately predict the hemolysis value when designing the axial flow blood pump. The movement behavior of a single RBC in the shear flow field was simulated at the mesoscale. The critical value of shear stress for physiological injury of RBCs was determined. According to the critical value, the equivalent treatment of RBC aging was studied. A novel hemolysis model was established considering the RBC's aging and the hemolysis's initial value. The model's validity was verified under the experimental conditions of shear stress loading and the conditions of the shear flow field of the blood pump. The results showed that, compared with other hemolysis models for estimating the hemolysis value of blood pumps, the novel hemolysis model proposed in this paper could effectively reduce the estimation error of the hemolysis value and provide a reference for the optimal design of rotary vane blood pumps.